2017
DOI: 10.3390/ijms18050982
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of the Tumor Suppressor PTEN by Hydrogen Peroxide and Tert-Butyl Hydroperoxide

Abstract: Organic peroxides and hydroperoxides are skin tumor promoters. Free radical derivatives from these compounds are presumed to be the prominent mediators of tumor promotion. However, the molecular targets of these species are unknown. Phosphatase and tensin homologs deleted on chromosome 10 (PTEN) are tumor suppressors that play important roles in cell growth, proliferation, and cell survival by negative regulation of phosphoinositol-3-kinase/protein kinase B signaling. PTEN is reversibly oxidized in various cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…To substantiate whether an identical intramolecular disulfide bond of PTEN was formed after 15s-HpETE treatment, lysates from MEFs treated with H 2 O 2 or the mixture of 15s-HpETE and Lipofectamine were fractionated on nonreducing gels and probed with PTEN antibody. Faster migrating bands, similar to those seen in our previous studies [30, 34, 36, 39], were detected following H 2 O 2 and a mixture of 15s-HpETE and Lipofectamine treatment (Figure 3(b)).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…To substantiate whether an identical intramolecular disulfide bond of PTEN was formed after 15s-HpETE treatment, lysates from MEFs treated with H 2 O 2 or the mixture of 15s-HpETE and Lipofectamine were fractionated on nonreducing gels and probed with PTEN antibody. Faster migrating bands, similar to those seen in our previous studies [30, 34, 36, 39], were detected following H 2 O 2 and a mixture of 15s-HpETE and Lipofectamine treatment (Figure 3(b)).…”
Section: Resultssupporting
confidence: 87%
“…We previously reported that exogenous organic peroxides and hydroperoxides can cause the irreversible oxidation of PTEN by impairing the cellular Trx system [34, 36]. The ability of lipid peroxides to oxidize PTPs has been reported previously [37], as well as the PTEN oxidation by unidentified arachidonic acid metabolites [38].…”
Section: Introductionmentioning
confidence: 94%
“…L-Histidine (3 mM) was added to some cells prior to irradiation to check for any 1 O 2 -mediated PTEN photooxidation; control cells received Lalanine at the same starting concentration. After irradiation, the cell medium was aspirated and replaced with 10% FBS-containing medium without or with L-His or L-Ala. At selected post-irradiation incubation times, non-oxidized thiol groups were blocked by treating cells with 20 mM NEM in lysing medium [20 mM Tris-Cl buffer (pH 7.4), 150 mM NaCl, 5% glycerol, 0.1% Nonidet-P40 detergent, and protease inhibitor mixture], followed by sonication and centrifugation [41]. Some cells served as positive controls by incubation with the known PTEN oxidant, H 2 O 2 (e.g.…”
Section: Examination Of Pten Oxidation Status After a Pdt Challengementioning
confidence: 99%
“…Supernatant fractions recovered after centrifugation were analyzed for total protein content by BCA assay, and then subjected to Western blotting under non-reducing conditions. Other details were as described by Zhang et al [41].…”
Section: Examination Of Pten Oxidation Status After a Pdt Challengementioning
confidence: 99%
See 1 more Smart Citation